2017
DOI: 10.1016/j.future.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-managing cloud-native applications: Design, implementation, and experience

Abstract: Running applications in the cloud efficiently requires much more than deploying software in virtual machines. Cloud applications have to be continuously managed : 1) to adjust their resources to the incoming load and 2) to face transient failures replicating and restarting components to provide resiliency on unreliable infrastructure. Continuous management monitors application and infrastructural metrics to provide automated and responsive reactions to failures (health management) and changing environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Similar research questions were found in works created by Sodhi et al (2011), Toffetti et al (2016), Kratzke and Quint (2017). However, they address different aspects of cloud-ready software development.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Similar research questions were found in works created by Sodhi et al (2011), Toffetti et al (2016), Kratzke and Quint (2017). However, they address different aspects of cloud-ready software development.…”
Section: Introductionsupporting
confidence: 57%
“…Here are just few examples of our findings. Andrikopoulos et al (2012), Toffetti et al (2016), Wilder (2012), Kratzke and Peinl (2016), Kratzke and Quint (2017) are using "cloud-native" term in their works and each of them provides a definition for it. "Cloud-ready" is mentioned by Brown and Capern (2014) from IBM, Kavis (2014), andWeinman (2016).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations